2006
DOI: 10.1089/apc.2006.20.848
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variability in Barriers Affecting People's Decision to Take HAART: A Qualitative Study Identifying Barriers to Being on HAART

Abstract: The efficacy of highly active antiretroviral therapy (HAART) has been well documented, particularly among HIV-infected individuals with CD4 cell counts below 200/mm(3). Despite this, eligible individuals may continue to show some reluctance to use HAART. The present study explored the factors influencing patients' decision not to take HAART even though it was medically indicated according to current treatment guidelines and available at no cost to the individual. Fifteen eligible patients at an urban HIV clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Others equated readiness with adherence to treatment or care [34–36•, 37•, 38]. For example, Wagner and colleagues [36•, 37•] measured readiness by which participants achieved >90% adherence as measured by an electronic monitoring device in a placebo trial.…”
Section: Resultsmentioning
confidence: 99%
“…Others equated readiness with adherence to treatment or care [34–36•, 37•, 38]. For example, Wagner and colleagues [36•, 37•] measured readiness by which participants achieved >90% adherence as measured by an electronic monitoring device in a placebo trial.…”
Section: Resultsmentioning
confidence: 99%
“…Among patients who have entered HIV care, fear of side effects, mistrust of medications and health care workers, concerns about the effects of medications on quality of life, and a preference for alternative medicine and self-care have been associated with lower acceptance of ART, 11,[13][14][15][16][17][24][25][26] although at least one study found no association between conspiracy beliefs and access to care. 27 However, research on the role of mistrust of medications and health care workers as barriers to entering care has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…14 These discussions should include a full assessment of the patient's values and sociocultural context as they relate to HIV care. 17 Although information about care and medications may be most accurately communicated by a medical provider, persons with negative perceptions of HIV medications may never enter a care relationship and therefore never have the opportunity to receive this information. In addition, as the experiences of NIC respondents indicate, they may not trust medical providers and thus prefer alternative therapies to information from the medical establishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the individual level of influence primary barriers to HIV care/ART for AABH-PLWH include negative health beliefs such as medical distrust, negative outcome expectancies, low levels of “readiness” [4852], and negative emotions about care/ART, including fear [5355]. Indeed, the primacy of fear as a barrier; namely, fear of being pressured to take ART in health care settings, of ART’s side effects and toxicities, and possible negative effects on relationships if on ART, cannot be over-stated [56, 57].…”
Section: Methodsmentioning
confidence: 99%